Direct synthesis of a solid calcium-silicate-hydrate (C-S-H). (30th October 2019) - Maddalena, Riccardo; Li, Kefei; Chater, Philip A.; Michalik, Stefan; Hamilton, Andrea
Highlights: Solid synthetic C-S-H is produced from calcium hydroxide and nano-silica. Shown to be crystallographically similar to the more commonly produced slurry. Curing time studies show significant C-S-H is produced after 1 day for C/S ratio = 0.81. Abstract: We present new results on solid (monolithic) synthetic C-S-H made at room temperature from easily obtainable calcium sources (calcium oxide, calcium hydroxide) and nanosilica (w/s = 2) with a 2 minute mixing time. Using synchrotron X-ray diffraction combined with TGA/DSC, 29 Si NMR and synchrotron pair distribution function (PDF) data we show that the solid C-S-H is crystallographically similar to the more conventionally made synthetic C-S-H slurry. We show that C-S-H is present after 1 day curing (C/S = 0.81) and no X-ray visible portlandite is present at day 3. PDF data shows that the ordered domain size is 2.5 – 4.5 nm, depending on the fit chosen.